Fabrication of innovative thermoplastic starch bio-elastomer to achieve high toughness poly(butylene succinate) composites. (15th February 2019) - Zhang, Shuidong; He, Yan; Yin, Yue; Jiang, Guo
Highlights: The impact strength of PBS/TPS increases from 2.8 to 6.3 KJ/m 2 when incorporated 2% tartaric acid. The toughening mechanism is ascribed that TPS-TA serves as bio-elastomer and uniformly disperses in PBS matrix in ellipse feature. TA elevates the compatibility of TPS and PBS matrix, while depresses the crystallization capability of PBS. Abstract: Sustainable biodegradable polymers with high performances is the optimized alternatives for resolving environmental key issues evoked by petroleum-based polymer. A novel bio-based elastomer was designed and developed using reactive extrusion for the mixtures of starch, glycerol and tartaric acid (TPS-TA). Then TPS-TA was extruded with PBS (30:70, wt%) to fabricate the bio-composites and the impact strength of PBS/TPS-TA was superior to that of PBS. The toughness mechanism was explored by analyzing the properties variations for the TPS-TA and PBS matrix, and their interfacial adhesion, systematically. Effects of TA on the structure of TPS and compatibility for PBS were evaluated by FT-IR, viscosity measurement, DSC, DMA and SEM, respectively. They revealed that TA reduced the molecular weight of starch and shear viscosity of TPS were beneficial for TPS-TA uniformly dispersing in PBS matrix as ellipse feature with 0.5 um averaged diameter. Simultaneously, TA also served as coupling effect to improve the compatibility of TPS and PBS matrix, and induce the morphology of bio-composites to transform from "sea-island" structure to homogeneous phase. Interesting, TPS-TA could depress the crystallization capability of PBS by the results of DSC, XRD and POM, which evidenced that the variations in the crystallization properties of PBS matrix are not responded to the impact strength improvement of PBS/TPS-TA. This study proposed a facile approach to fabricate low-cost PBS bio-composites with significant improved mechanical properties.